Applications of environmental chemistry : a practical guide for environmental professionals - Weiner, Eugene R. (Lewis Publishers, 2000)
Water quality.--Principles of contaminant behavior in the environment.--Major water quality parameters.--Soil, groundwater, and subsuface contamination.--Petroleum releasesto the subsurface.--Selected topics in environmental chemistry.--A dictionary of inorganic water quality parameters and pollutants.